Approach to Acute Respiratory Illness in Children with Hematological Malignancy: A Prospective Study Evaluating Utility of CT Scan - Aggarwal, Priyanka; Raipa, Tapish; Kumar, Ishan; Verma, Ashish; Shukla, Ram Chandra; Gupta, Vineeta (Indian Journal of Medical and Paediatric Oncology, 2022)
Introduction Various pulmonary complications can occur in children with hematological malignancies including both infection and malignant disease infiltration of pulmonary parenchyma.Objectives To assess the role of CT scan in determining the etiology of acute pulmonary complications in children with hematological malignancies.Materials and Methods All children < 17 years with newly diagnosed hematological malignancy with respiratory symptoms (Group A) along with children who developed fever with persistent respiratory symptoms as well as worsening chest radiographs during treatment (Group B) and underwent CECT thorax, from February 2019 to July 2020 were enrolled. The final diagnosis was made on the basis of clinical history, laboratory as well as radiological investigations and treatment response.Results Thirty-seven children with mean age of 7.5 ± 3.5 years and male to female ratio of 1.3:1 who underwent CECT thorax were included in our study. For newly diagnosed cases, i.e., Group A (n = 8), the most common cause of respiratory symptoms as identified on CECT thorax was pulmonary tumoral infiltration (n = 5) followed by tuberculosis (n = 3). However, in Group B (n = 29) the cause of persistent respiratory symptoms was identified as infection (n = 17) followed by leukemic infiltration (n = 12). Thus, chest CT could accurately identify pulmonary tuberculosis, fungal pneumonia, bacterial infection, and pulmonary tumoral infiltrates.Conclusion CT scan can be used as an adjunctive tool for prompt diagnosis and management of pulmonary complications in children with persistent respiratory symptoms as they are often non-specific.
Keywords: contrast-enhanced computed tomography; leukemia; lymphoma; lungs; pediatric